STRUCTURES FOR WOVEN-LIKE KNITTING FABRICS MADE ON CIRCULAR KNITTING MACHINES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
In this article, options for woven-like knitting structures on a crochet basis are considered worked on circular knitting machines. Technical and technological parameters for their production are described. Nine variants to achieve knitting on type of a double-faced and an interlocking basis have been developed. In both groups, sub-variants with the presence or absence of press elements are proposed. The cylinder and disc rows with two types of needles – short and long are presented in tabular form. The all structures were successfully knitted on the circular knitting machine.